2010
DOI: 10.1134/s0362119710010068
|View full text |Cite
|
Sign up to set email alerts
|

Activation and inhibition of bimanual movements in school-aged children

Abstract: The development of motor activation and inhibition was compared in 6 to 12 year olds. Children had to initiate or stop the externally paced movements of one hand, while maintaining that of the other hand. The time needed to perform the switching task (RT) and the spatio temporal variables show different age related evolutions depending on the coordination pattern (in or anti phase) and the type of transition (acti vation, selective inhibition, non selective inhibition) required. In the anti phase mode, activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
1
2
0
1
Order By: Relevance
“…Moreover, TD children increase their capacity to maintain the stability of the tempo of the left continuing finger. This finding is in accordance with previous results using a similar experimental task (Barral et al, 2010) and comforts the results of Roy, Bryden, and Cavill (2003) who found that the control of non-preferred hand improves during typical childhood. These results highlight an age-related increase in the role of the non-dominant (left) hand in bimanual coordination and motor switching in the normal time course of development.…”
Section: Improvement In Control (Inhibition and Maintain) Of The Leftsupporting
confidence: 95%
“…Moreover, TD children increase their capacity to maintain the stability of the tempo of the left continuing finger. This finding is in accordance with previous results using a similar experimental task (Barral et al, 2010) and comforts the results of Roy, Bryden, and Cavill (2003) who found that the control of non-preferred hand improves during typical childhood. These results highlight an age-related increase in the role of the non-dominant (left) hand in bimanual coordination and motor switching in the normal time course of development.…”
Section: Improvement In Control (Inhibition and Maintain) Of The Leftsupporting
confidence: 95%
“…Neural crosstalk occurs when both hemispheres send motor commands to the contralateral limb via the crossed corticospinal pathways while simultaneously sending a mirror image of the motor command to the ipsilateral limb via the uncrossed corticospinal pathways (Cattaert et al, 1999;Cardoso de Oliveira, 2002). This ipsilateral influence may alter the activation of the involved muscle (Cattaert et al, 1999;Swinnen, 2002) resulting in increased or decreased contralateral muscle activation depending on whether the motor command is excitatory or inhibitory (e.g., Barral et al, 2006Barral et al, , 2010. With training, individuals can often compensate for neural crosstalk that is dispatched to the contralateral limb (Barral et al, 2006(Barral et al, , 2010.…”
Section: Bimanual Coordinationmentioning
confidence: 99%
“…This ipsilateral influence may alter the activation of the involved muscle (Cattaert et al, 1999;Swinnen, 2002) resulting in increased or decreased contralateral muscle activation depending on whether the motor command is excitatory or inhibitory (e.g., Barral et al, 2006Barral et al, , 2010. With training, individuals can often compensate for neural crosstalk that is dispatched to the contralateral limb (Barral et al, 2006(Barral et al, , 2010. However, the failure to inhibit, suppress, or otherwise compensate for the neural crosstalk may result in unintended motor actions (Houweling et al, 2010).…”
Section: Bimanual Coordinationmentioning
confidence: 99%
“…Совершенствование профилактики нервно-психиче-ских нарушений у детей требует их ранней диагностики в условиях современной школы [10]. Длительность форми-рования регуляторных систем в младшем школьном воз-расте и их роль в организации когнитивной деятельности подтверждена в нейропсихологических и психометриче-ских исследованиях [11][12][13][14].…”
unclassified